Jews in the Netherlands A Short History - Levie Bernfeld, Tirtsah (Amsterdam University Press, 2023)
Most people know little more than fragments of Dutch Jewish history: the Portuguese Jews of Amsterdam; Jewish socialism; the devastating years of the Second World War. So where is the storyline? What happened to the Jews in the Netherlands from the moment they first settled there permanently? This book answers that question. It presents the central points of 700 years of Jewish history in the Netherlands briefly and succinctly. One hundred elements of the story have been chosen that taken as a whole create a balanced and representative picture. Each relates to a central event, place, person or object that helps to illuminate one important aspect of the history of the Jews in the Netherlands, and each is linked to a striking, iconic image. They are grouped by century around unifying themes that make them part of an ongoing story.